(untitled) (Ustozlar uchun, 2026)
This article examines the significance of interactive methods in the process of teaching and learning English. Interactive teaching approaches encourage active student participation, enhance communication skills, and create a learner-centered educational environment. The paper discusses various interactive techniques, including group discussions, role-playing activities, brainstorming, project-based learning, and digital educational tools. Furthermore, it highlights the advantages of these methods in improving language proficiency, critical thinking, creativity, and learner motivation. The study emphasizes that the effective implementation of interactive methods contributes significantly to the development of communicative competence in English language learners.